Penyuluhan Kesehatan Tentang Sadari Sebagai Upaya Promosi Kesehatan Pada Remaja Di Klinik Ismawati Desa Dalu 10 A Kecamatan Tanjung Morawa Kabupaten Deli Serdang, Sumatera Utara - Rangkuti, Saddiyah; Hayati, Nila; Zaen, Niasty Lasmy; Lubis, Anita Damayanti; Pase, Muslimah (CV. Devi Tara Innovations, 2024)
This community service activity aims to increase young women's knowledge about BSE (Breast Self-Examination) and identify factors that influence BSE behavior. This study used a quantitative survey design with cross-sectional data collection through the distribution of questionnaires to adolescent girls at Ismawati Clinic, Dalu 10 A Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra. The study population was all adolescent girls, with statistical analysis including frequency distribution, chi-square, and logistic regression. The results showed that 84% of respondents did not do BSE. Variables that are significantly related to BSE behavior are attitudes, family history, media information, and family influence. The most dominant variable is mass media information with an OR value of 16,295, which means respondents who are exposed to media information have a 16 times greater chance of self-awareness than those who are not exposed to media information. Community service activities were carried out by students of the University of Hajj North Sumatra on May 21, 2024, with the initial stage explaining the definition, benefits, and procedures for conducting BSE, as well as the distribution of related leaflets. The results of the activity showed that participants responded positively and actively participated in discussions and questions and answers. The increasing incidence of breast cancer shows the importance of self-awareness, especially among adolescent girls, for early detection. It was concluded that health counseling through video media is effective in increasing knowledge about BSE, and it is recommended that schools use video media as teaching materials related to breast health and early detection of breast cancer. This activity was considered successful with a positive response from participants.